The Power of Peers in Employee Assistance: A Unique Program for a Community College - Docherty, Oonagh; Bucklee, Joanne; Hills, Marcia D.; Johnson, Peggy; Michalenko, Cathy (Canadian Journal of Counselling and Psychotherapy, 2011)
Employee Assistance programs have traditionally been directed from near the top of an institutional or organizational structure, and have typically focused on addiction problems affecting job performance. The Red Deer College program REACH (Resources for Employee Assistance, Counselling and Health) has moved beyond this traditional approach to become an autonomous program run by employees for employees. The program is concerned with the general well being of workers at the college. This paper describes the REACH program with a particular emphasis on the innovative development of the Peer Support program.